ANALISIS PANJANG ANTRIAN KENDARAAN AKIBAT KENDARAAN YANG MELAKUKAN PUTARAN BALIK DI AREA U-TURN (STUDI KASUS : JL. KOL. H. BURLIAN KM. 9 PALEMBANG) - Putra, Dyan Pratnamas; Buchari, Erika; Arliansyah, Joni (FSTPT Indonesia, 2015)
Queues vehicle in U-turn area occur because of vehicle that does U-turn will take 1 lane in as a result there’s no lanes of vehicle waiting before do U-turn. Moreover, the vehicles that do U-turn will take 2 lanes in from opposite directions as consequence vehicle maneuver against the turning radius in the median. Reduction lanes from 3 to 2 lead to a narrowing of the road due to queue of vehicle waiting before U-turn. From the above, it can be concluded that the delay time in U-turn area caused by queuing vehicle that do U-turn. From time delay issues in U-turn area, we need study / research the influence queues length of vehicles in U-turn area. The purpose of this study was to analyze the road capacity, queues length and travel times of vehicle before and after the change in U-turn area design using VISSIM 6.0.The methodology used in this research is the vehicle volume survey counting, vehicle travel time, U-turn vehicle travel time and the number of vehicle arrival in U-turn area at Jl. Kol. H. Burlian km. 9 Palembang. We analyze the road capacity, long queues of vehicles travel time in the existing condition and new road design plan condition in U-turn area with manual calculation and VISSIM 6.0 programme.From the research, it is found that the road capacity is reduced from 3 lanes (4226 smp/hour) to 2 lanes (2762 smp/hour) and maximum vehicles queue length is 45,89 m. From these result we made the design plan of new road in U-turn area at Jl. Kol. H. Burlian Km. 9 Palembang, with the addition of a special vehicle lane doing U-turn (3,13 m width ; 45 m length) and additional road median for 7 m (from existing condition 2 m to 9 m). Overall planning of road widening in U-turn area is 13,26 m (left width 6,63 m and right wide 6,63 m). In addition, we need to add a road divider marking for vehicle queuing discipline that will do U-turn.From the analysis of the road new design at Jl. Kol. H. Burlian Km. 9 Palembang, we can conclude that a reduction in maximum queue length from 45,89 m (existing condition) to 0,00 m (new road design), besides there is reduction in maximum vehicle travel time from 7,45 second (existing condition) to 2,475 second (new road design).